Swedish election study 1994 - Holmberg, Sören; Gilljam, Mikael; Statistics Sweden (University of Gothenburg, 1997)
This is the thirteenth election study carried out in Sweden in connection with a Swedish general election. Many of the questions are replications of questions asked in one or several of the previous surveys, but there are also a number of questions not asked before. The interview included questions on how much the respondent takes part of political matters in mass media; political interest in general and political discussions among family and friends; important issues when deciding how to vote; opinion on which of the smaller parties will receive at least 4% of the votes; and preferred formation of the government after the election. There were also a number of questions on the opinions of the political parties regarding: employment, environment, taxes, the Swedish economy, energy and nuclear power, foreign affairs and security policy, social safety, child care, EU, refugees, law and order, equality between men and women, and education. Political parties, party leaders and other key politicians, and different groups and organizations were to be placed on a scale ranging from strongly dislike to strongly like. The respondents also had to state how much confidence they had in Swedish politicians and to give marks from -5 to +5 for different formations of government during the two last decades. They also had to indicate what they considered most important to fight against, unemployment or inflation, and to state their opinion on nuclear power. Furthermore there were a number of questions concerning a Swedish EU-membership: the opinion of the respondent, reason for being for/against a Swedish membership, opinion of different political parties. Other questions dealt with the kind of society preferred and how worrying for the future one considered following things to be: environmental damage, economic crise, situation in Russia, increasing number of refugees, unemployment, increasing violence, the risk of Sweden being included in a war, and the risk of Sweden being less democratic. The respondent also had to place people in general on three different scales concerning selfishness, trustworthiness, and knowledge what is best for themselves. The respondent also had to place herself/himself on all these scales. A number of questions dealt with party preference; vote in the September elections and at the EU referendum; things important when choosing party; votes in earlier elections. As in earlier election studies the respondent had to place the political parties on a political left-right scale. In this survey the political parties also had to be placed on a green dimension scale, a EU-opinion scale, a refugee acceptance scale, and a equality between men and women scale. The respondent also had to place herself/himself on all these scales.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

This is the thirteenth election study carried out in Sweden in connection with a Swedish general election. Many of the questions are replications of questions asked in one or several of the previous surveys, but there are also a number of questions not asked before. The interview included questions on how much the respondent takes part of political matters in mass media; political interest in general and political discussions among family and friends; important issues when deciding how to vote; opinion on which of the smaller parties will receive at least 4% of the votes; and preferred formation of the government after the election. There were also a number of questions on the opinions of the political parties regarding: employment, environment, taxes, the Swedish economy, energy and nuclear power, foreign affairs and security policy, social safety, child care, EU, refugees, law and order, equality between men and women, and education. Political parties, party leaders and other key politicians, and different groups and organizations were to be placed on a scale ranging from strongly dislike to strongly like. The respondents also had to state how much confidence they had in Swedish politicians and to give marks from -5 to +5 for different formations of government during the two last decades. They also had to indicate what they considered most important to fight against, unemployment or inflation, and to state their opinion on nuclear power. Furthermore there were a number of questions concerning a Swedish EU-membership: the opinion of the respondent, reason for being for/against a Swedish membership, opinion of different political parties. Other questions dealt with the kind of society preferred and how worrying for the future one considered following things to be: environmental damage, economic crise, situation in Russia, increasing number of refugees, unemployment, increasing violence, the risk of Sweden being included in a war, and the risk of Sweden being less democratic. The respondent also had to place people in general on three different scales concerning selfishness, trustworthiness, and knowledge what is best for themselves. The respondent also had to place herself/himself on all these scales. A number of questions dealt with party preference; vote in the September elections and at the EU referendum; things important when choosing party; votes in earlier elections. As in earlier election studies the respondent had to place the political parties on a political left-right scale. In this survey the political parties also had to be placed on a green dimension scale, a EU-opinion scale, a refugee acceptance scale, and a equality between men and women scale. The respondent also had to place herself/himself on all these scales.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1994
VU94
Keywords: elections; val; politics; politik; voting intention; röstavsikt; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; election broadcasting; valbevakning i tv och radio; government policy; regeringspolitik; political allegiance; politisk anhängare; political participation; politiskt deltagande; government; regering; electors; väljare; internal politics; inrikespolitik; party politics; partipolitik; political parties; politiska partier; social policy; politik (policy); political leaders; politiska ledare; election campaigns; valkampanjer; electoral issues; valfrågor; opposition parties; oppositionspartier; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; political issues; politiska frågor; lobbying; politisk påverkan; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap